The Uses and Consequences of Literacy Among Salvadoran Campesinos/as: A Longitudinal Study - Esther Prins (Adult Education Research Conference, 2008)
This paper uses data from a longitudinal study with former adult literacy participants in El Salvador to examine how campesinos/as currently use literacy and what they perceive as the temporary and long-term socio-economic benefits of literacy education. The findings underscore the social dimensions and multi-faceted nature and consequences of literacy.
Keywords: adult literacy; El Salvador; international adult education; literacy practices